The sociology of Anthony Giddens - Loyal, Steven (Pluto Press, 2003)
"Anthony Giddens is one of the most famous and influential sociologists of recent decades. Largely credited with the concept of the "Third Way", he continues to be a key advisor to Tony Blair ... This original and controversial book provides an excellent introduction to Giddens' work, covering the wide range of his writing from theory to self-reflexivity, modernity and politics, placing them all within the illuminating framework of a historical context. Steven Loyal argues that Giddens' writing has always embodied a political and ethical position, one that has changed considerably over the years and is best understood through the social context in which it was written. Providing a comprehensive overview of Giddens' writing, Loyal explores the many tensions and failures in Giddens' theory and argues that, overall, his work is fundamentally flawed."--Book cover
Keywords: Giddens, Anthony.; Giddens, Anthony -- Contributions in political science.; Giddens, Anthony; Sociology -- Philosophy.; Social structure.; Civilization, Modern.; Sociologie -- Philosophie.; Structure sociale.; Civilisation moderne et contemporaine.; social structure.; SOCIAL SCIENCE -- Regional Studies.; SOCIAL SCIENCE -- Anthropology -- General.; SOCIAL SCIENCE -- Sociology -- General.; Civilization, Modern; Political science; Social structure; Sociology -- Philosophy; Soziologie; Soziologische Theorie; Einführung; Sociologen.; Sociale structuur.; Politieke sociologie.